2020
DOI: 10.3390/w12041216
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based Analysis of Runoff Generation Processes in Humid Lowlands of the Taihu Basin, China

Abstract: In the flat lowland agricultural areas of subtropical climate zones, the runoff process has a great influence on the regional water quantity and quality. In this study, field data about rainfall, evapotranspiration, soil moisture, groundwater table, and surface water dynamics were collected in two different experimental sites in the Taihu Basin, China. Results showed that densely distributed ditches contributed to shallow groundwater depths and persistent near-saturation soil. A correlation analysis was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Though agriculture is dominant in the basin, the economic background of the farmers is quite low here in comparison to the rest of the country as agriculture is heavily dependent on rainfall and the irregular and erratic nature of has damaged many of them. As hydrology plays an important role in determining the growth of agricultural sector; therefore, studying the impact of climate variability on hydrology [32][33][34][35] is a major issue of concern. Hence, the pivotal role of climate in agriculture sector, the principal source of livelihood of the population and low economic background of the farmers in and around the basin, motivated the authors to investigate the impact of climate variability on streamflow [36][37][38][39] in terms of various climatic parameters in the basin region.…”
Section: Introductionmentioning
confidence: 99%
“…Though agriculture is dominant in the basin, the economic background of the farmers is quite low here in comparison to the rest of the country as agriculture is heavily dependent on rainfall and the irregular and erratic nature of has damaged many of them. As hydrology plays an important role in determining the growth of agricultural sector; therefore, studying the impact of climate variability on hydrology [32][33][34][35] is a major issue of concern. Hence, the pivotal role of climate in agriculture sector, the principal source of livelihood of the population and low economic background of the farmers in and around the basin, motivated the authors to investigate the impact of climate variability on streamflow [36][37][38][39] in terms of various climatic parameters in the basin region.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also does not consider saturated excess rainfall based on antecedent rainfall or Dunne flow, which may be an equally important mechanism for determining runoff risks [56,57]. Finally, the source of infiltrating water is not limited to direct rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The Gibbs plot results indicated that the hydrochemical characteristics of groundwater in the Lake Taihu Basin were mainly affected by rock weathering and dissolution. The soil in the study area is often saturated due to high precipitation (Zhai et al 2020) and, in this case, the minerals in the rock continue to dissolve. Dissolved minerals are then leached into shallow groundwater by the infiltration of rainfall, resulting in differences in the composition of anions and cations in groundwater across different areas (Alyamani et al 1995;Subramani et al 2010;Ye et al 2010).…”
Section: Discussionmentioning
confidence: 99%